Environmental effects on viscoelastic behavior of carbon fiber/PEKK thermoplastic composites - Mazur, Rogerio L. [UNESP]; Oliveira, Pedro C.; Rezende, Mirabel C.; Botelho, Edson C. [UNESP] (Sage Publications Ltd, 2014)
In the last years, thermoplastic composites have been introduced as structural materials for high performance aerospace applications. However, these materials can present problems when exposed to moisture, temperature, and UV radiation, and besides it may occur as the synergy among the main degradation mechanisms. Among the thermoplastic composite materials, carbon fiber reinforced poly(ether-ketone-ketone) (PEKK) laminates have shown excellent balance of properties, including high glass transition temperature, high strength, stiffness and fracture toughness values, low moisture absorption, and good environmental resistance. The aim of the present work was to evaluate the influence of the environmental effect on the viscoelastic behavior and glass transition temperature of carbon fiber reinforced PEKK thermoplastic composites. In this work, the effects of environmental degradation on the viscoelastic properties of this composite material were studied by dynamic mechanical analyses. The most significant change was observed for the UV radiation accelerated weathering conditioning effects. A decrease of the storage modulus from 40 to 10 GPa and the Tg from 147 to 105celcius is observed, which decreases consequently the composite stiffness and the service temperature after exposed environmental effects. A synergetic degradation mechanism between UV radiation accelerated weathering test and hygrothermal conditioning is clearly verified.
Keywords: environmental degradation; Polymer-matrix composite; dynamic mechanical analysis